Characterization of Staphylococcus aureus Strains Isolated from Veterinary Hospital - Ariel E. Stella; Thaís F. Lima; Cecília N. Moreira; Eric M. N. De Paula (International Journal of Microbiology)
This study aims to detect Staphylococcus aureus (S. aureus) resistance in the veterinary hospital environment. S. aureus are one of the components of the microbiota, and they may be present in patients in a veterinary hospital environment. Methicillin resistance is determined by a chromosomal gene (mecA), which codes for modifications in the beta-lactam antibiotic receptor, where the penicillin-binding protein will have a low affinity for the antibiotic. Samples were collected through swabs of materials and equipment at the hospital. S. aureus was identified in 7.6% (21/276) of the samples collected, and of the 21 strains isolated, 4 (19.0%) carried the mecA gene. MRSA are all strains of S. aureus that express the mecA gene. Four strains harbor the mecA gene; however, only two expressed the phenotypic resistance to cefoxitin and were characterized as MRSA. An isolate (strain 18) present on a patient care table was identified as methicillin-resistant S. aureus with intermediate sensitivity to vancomycin (VISA). Our observations suggest the need for containment measures (good antisepsis practices) to avoid the possible transmission of resistant bacterial agents for the veterinary hospital environment.